2008
DOI: 10.1007/s00167-008-0559-1
|View full text |Cite
|
Sign up to set email alerts
|

Knee anterior laxity: a risk factor for traumatic knee injury among sportswomen?

Abstract: The purpose of this study was to investigate if knee anterior laxity, measured with an arthrometer, is a risk factor for traumatic knee injury in sportswomen. To allow a more complete analysis, other, easily measured variables such as anthropometry, lower leg characteristics, sport exposure and menstrual cycle characteristics were also evaluated as possible risk factors. Subjects were Slovenian sportswomen aged between 11 and 41 years participating in basketball, team handball and volleyball (N = 540). Sportsw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 38 publications
(60 reference statements)
1
44
0
1
Order By: Relevance
“…Since female reproductive hormones could be a key factor that have an impact on musculoskeletal structure, future study should divide women into two groups: women with a normal menstrual cycle and women with ingesting OCP. Also, in previous studies, researchers found the greatest ACL elasticity and less knee stiffness during ovulation where estrogen concentration in the blood was highest compared to menstruation where estrogen concentration was lowest in young healthy women with a regular menstrual cycle (Zazulak et al 2006;Vauhnik et al 2008;Park et al 2009). This was believed to be caused by both estrogen and temperature fluctuation during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Since female reproductive hormones could be a key factor that have an impact on musculoskeletal structure, future study should divide women into two groups: women with a normal menstrual cycle and women with ingesting OCP. Also, in previous studies, researchers found the greatest ACL elasticity and less knee stiffness during ovulation where estrogen concentration in the blood was highest compared to menstruation where estrogen concentration was lowest in young healthy women with a regular menstrual cycle (Zazulak et al 2006;Vauhnik et al 2008;Park et al 2009). This was believed to be caused by both estrogen and temperature fluctuation during the menstrual cycle.…”
Section: Discussionmentioning
confidence: 89%
“…*Significant changes from resting. Griffin et al 2000;Zazulak et al 2006;Vauhnik et al 2008). Higher level of estrogen makes women more susceptible to injuries (Chaudhari et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We referred to these data as the preseason testing data; analysis of these data has been published. 12,13 At the same time, information for the following variables was collected: age, height, mass, age at menarche, use of oral contraception, regularity of menstrual cycle, duration of sport participation, training and game exposure per week, leg dominance, knee-extension passive range of motion, navicular drop, and knee anterior laxity at 3 different forces (15 Twelve teams were excluded from the analysis because they either did not complete the postseason questionnaire (2 basketball, 4 team handball, and 5 volleyball teams) or withdrew from the study (1 basketball team; no reason stated). The study was thus completed by 43 clubs and 585 athletes (49% of the target population).…”
Section: Methodsmentioning
confidence: 99%
“…Характерен ме-ханизм травмы, при котором происходит пере-разгибание голени в коленном суставе либо ее скручивание. При этом больные часто отмечают щелчок [1][2][3]. Часто при разрывах ПКС в пер-вые 24 часа возникает гемартроз коленного су-става, иногда в подколенной области появляется гематома [4].…”
Section: Introductionunclassified